Feeding traits and dietary variation in Pleistocene proboscideans: A tooth microwear review. (1st September 2019) - Rivals, Florent; Semprebon, Gina M.; Lister, Adrian M.
Abstract: Microwear data were analysed to study dietary traits in Elephantidae, Mammutidae, and Gomphotheriidae from Plio-Pleistocene localities from Europe and North America and included the following taxa: Palaeoloxodon antiquus, Mammuthus rumanus, M. meridionalis, M. trogontherii, M. primigenius, M. columbi, Mammut americanum, and Anancus arvernensis . Mammuthus shows a wide variety of dietary strategies, with an overall trend from browsing to grazing through the lineage from M. rumanus to M. primigenius . Nonetheless there is significant inter-population variability which is clearly related to the resources available or to limitations imposed by competition and niche partitioning with other large herbivores. Among the species, Mammuthus columbi (Late Pleistocene of North America) displays both browsing and grazing populations and individuals and also shows heavier pitting than the other species of Mammuthus studied, possibly indicating the occupation of a more arid habitat. The Middle and Late Pleistocene Palaeoloxodon antiquus from Europe also shows dietary plasticity, with browsing, grazing and mixed feeding patterns observed. Dietary variability appears to be lower in Mammut americanum from North America and Anancus arvernensis which were apparently committed browsers (except the grass-dominated mixed feeding A. arvernensis from Norwich Crag). Our results reveal interesting patterns involving Pleistocene vegetation structure and climate as well as aspects of niche utilization. Highlights: Palaeodiet of proboscideans from the Plio-Pleistocene of Europe and North America. Significant inter-population variability in most taxa. Trend from browsing to grazing through the lineage from M. rumanus to M. primigenius . Increased crown height in Proboscideans permitted to expand their dietary breadth.